Corporatisation of universities librarian's perspective - Zaiton Osman (UKM, Bangi : Perpustakaan Tun Seri Lanang, 1996)
A talk on corporatisation of library in Universiti Malaya
The talk was given in conjunction with'Minggu Perpustakaan Tun Seri Lanang' 9-13 Jan., 1996 in Bangi
Copy available in DVD format
Keywords: Library administration -- Malaysia; Organizational change; Libraries and society; Academic libraries -- Malaysia